Empowering Junior High School English Teachers to Integrate Intercultural Communicative Competence in English Language Teaching - Ida Bagus Nyoman Mantra; Anak Agung Putri Maharani; I Kadek Dian Satriawan; Sang Ayu Putu Ichita Dewi; Ni Luh Putu Anggi Widyantari; Ni Made Lovi Arini (Abdimas Indonesian Journal, 2026)
Intercultural Communicative Competence (ICC) has become an essential component of English language teaching as educators are expected to prepare learners to communicate effectively in culturally diverse contexts. However, many English teachers still emphasize language proficiency but struggle to incorporate intercultural perspectives into their classroom instruction. The community service was designed to strengthen the Intercultural Communicative Competence of junior high school English instructors through a participatory professional development program. The program was conducted with English teachers from five junior high schools in Gianyar Regency, Bali, Indonesia. The program ran for 8 weeks, incorporating collaborative workshops, lesson planning, classroom mentorship, reflective practice, and peer discussion. Pre-test and post-test, classroom observations, evaluation surveys, and semi-structured interviews were used to collect the data. Results showed that all aspects of ICC improved significantly. The overall mean ICC score rose from 63.5 on the pre-test to 88.0 on the post-test. Teachers also had very positive perceptions of the curriculum, reporting enhanced professional confidence, stronger lesson-planning abilities, and greater preparedness to adopt intercultural pedagogy in English classrooms. The study finds that participatory professional development is an effective and sustainable approach to developing teachers' intercultural competence and supporting culturally responsive English language instruction.